PENGARUH PEMBELAJARAN BERHITUNG JARIMATIKA TERHADAP MINAT BELAJAR MATEMATIKA ANAK USIA SEKOLAH DASAR - Dwi Putri Idiyani , Arsita (Educational Psychology Journal, 2012)
Education is one important sector in the development of each country. According to Law No. 20 Year 2004 education is aconscious and planned efforts to develop the potential of all learners through the learning process. Learning occurs in interaction with the environment, socially, and in the face of every event. Basically, learning is a mental activity / psyche that took place in an active interaction with the environment produce changes in knowledge, understanding, skills and attitude values.Jarimatika learning is a source for learning, while the tutor or lecturer jarimatika an auxiliary force and the fingers used in thelearning process is a facility. Adjustment to the individuals who preferred teaching is about teaching and learning methods,teaching techniques, and how the lesson settings. In his research note that student achievement in learning can be enhancedwith effective learning methods include the spirit of learning and cultivate students' interest in learning. This learning processcan be said to succeed when it educates students successfully completed the tasks in the study with satisfactory values commonly called achievements. Elementary Students Islamic Prince Diponegoro Class II, III, and IV are also experiencing problems in math class values. There are many factors that affect achievement in mathematics one of them interest in learningmathematics. Enthusiasm is a feeling of interest in a matter or activity without affecting. Students' interest in the learningprocess can be shown by the existence of a sense of interest to learn sunguh-indeed, the willingness to always be active in learning activities. This study aims to describe students' interest in learning elementary school mathematics and numeracy learning effect jarimatika to increase interest in learning mathematics. The subjects were 28 students who were taken by using sampling techniques such as purposive sampling. This research was conducted with experimental methods of re-design of experiment (quasi-experimental) with the type of experimental pre non randomized pretest-posttest one group design. Samples were divided into two groups namely experimental group and control group with the number of members of each group of 28 subjects. Research data capture is performed using a scale interest in learning mathematics with the reliability coefficient of 0.946 and from 60 items 50 items found valid. Data analysis using t-test test techniques with the help of a computer program (SPSS) version 12 for windows. Results of analysis of data obtained by using t-test, the correlation between two variables, which produces the number 0.599 with probability value well below 0.05 (see the significant value of output is 0.001). This suggests that the correlation between the average interest in learning mathematics before and after learning to count jarimatika is significant. While the look of the probability (Sig. two tailed) is 0.000. hence the probability <0.05, then the nil hypothesis Ho is rejected pretest may imply that there are differences in the level of interest in learning mathematics between the experimental groups before and after learning to count jarimatika. So we can conclude that learning jarimatika effective to increase interest in learning math elementary school children in elementary Pengeran Islam Diponegoro, thereby Ha accepted. Description of interest in learning mathematics experienced by elementary school students tend to Islam Diponegoro in aspects of attention, interest, and desire. Based on the results of the study concluded that learning arithmetic jarimatika effective to increase interest in learning mathematics. Hence the advice given to this jarimatika numeracy learning activities continued to be held as well as add other activities as efforts to increase the creativity of learning in all lessons.